Experimental study on the control of HVAC system - Ng, Yu Lin (Nanyang Technological University, 2021)
This report presents on the experimental study that was done based on the aim of achieving accurate airflow measurement. Airflow measurement is a pre-requisite to achieve a balanced air flow system. Based on existing research, there been evidences to support that it is important to have a precise flow measurement to ensure that a balanced system in the air distribution system which will address thermal comfort, ensuring system efficiency and energy savings in the long run during operational days.